On the cusp of mediating poverty: phenomenal experience and fear - Suman Gupta (Alea: Estudos Neolatinos, 2019)
This paper presents some conceptual observations on how the condition of poverty is brought to public attention and discussed, i.e. on mediations of poverty. It is proposed that such mediation is largely monopolised by those who are not-poor, though attempts to describe the not-poor as a category call for circumspection. As such, mediations are based on preconceptions which are seldom examined carefully. These preconceptions are dubbed phenomenal bases here, and three are outlined in general terms: poverty as experience, visible poverty, and poverty in abstract. A final section considers ‘fear of poverty’ as a pervasive idea, and speculates on the possibility of approaching political economy accordingly.